Index of the Cycle of Money - The Case of Canada - Challoumis, Constantinos (Journal of Entrepreneurship, Business and Economics; Vol 11 No 1 (2023), 2023)
The purpose of this paper is to apply the theory of the monetary cycle to the case of Canada. In previous works, the economic characteristics of Latvia, Serbia, Bulgaria, Greece, Thailand, and Ukraine were determined according to the concept of the theory of the circulation of money. The money circulation index provides guidance on how an economic system should counteract a currency crisis and examines how well a country’s economy is structured. Canada's money cycle index estimates are compared to the world's average money cycle index. The results show that Canada is above the global average. Canada’s results show that it is a leading economy and can deal with an economic crisis immediately and in a very short time, as leading economies should. The methodology used is based on the analysis of theory and mathematical, statistical, and econometric results. The current work is important because it presents the strength of the Canadian economy in the face of a possible financial and economic crisis. This work comes from a project for several countries. The recent decision to impose a minimum tax of 15% on international corporations is consistent with the fixed-length principle of the theory of the monetary cycle. The money cycle index or index of the cycle of money makes it possible to address questions about the strength of the economy, considering the economy as an entity that interacts with other economies. The case of Canada shows that its economy has an index of money circulation of 0.88, which means that it is one of the excellent economies and can recover from any economic crisis in 2 to 5 years, depending on how well the authorities will respond to an economic crisis. A value of 0.1 means that it takes 2 to 5 years for an economy to recover from its strength. The ideal economy has a value of 1 on the money circulation index (index of the cycle of money). An economy with a value of 1 can respond immediately to an economic crisis, and this is an ideal level for any economy. Every 0.1 less than 1 means that the economy will take 3 to 5 years to recover. The money cycle index is a unique index that measures the strength of any economy. This work is the only work that can be found in the current bibliography on the money cycle. In addition, this paper is a unique work that shows that tax evasion does not harm the economy but causes a delay in tax revenues, and at the same time tax evasion harms the economy. Research paper Keywords: The cycle of money; Canada; Index of the cycle of money Reference to this paper should be made as follows: Challoumis, C. (2023). Index of the Cycle of Money - The Case of Canada. Journal of Entrepreneurship, Business and Economics , 11 (1), 102–133.